2017
DOI: 10.1590/s1677-5538.ibju.2016.0269
|View full text |Cite
|
Sign up to set email alerts
|

Urethral duplication type influences on the complications rate and number of surgical procedures

Abstract: Introduction:Urethral duplication is rare. Characterized by the presence of two urethral channels. This anomaly presents a great variety of clinical findings that depend on the type of duplication that often is associated with other anomalies.Material and Methods:We report thirteen boys with urethral duplication managed in our institution between 1988-2015. Clinical findings, associated anomalies, treatment of urethral duplication and our results are described. Patients were classified according to Effmann cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
(20 reference statements)
0
9
0
2
Order By: Relevance
“…Lopes and his colleagues reported that the type of UD was associated with the number of surgeries needed and the postoperative complication rate. 17 Mane SB et al described a single-stage repair protocol in which the buccal mucosa forms a tube for urethroplasty in cases of Y-duplication and reported it achieved good final outcomes. 18 Mori et al described a case treated with complete excision of the accessory urethra from the normal urethra in a rare type IIA2 (Y-type) patient who had an accessory urethra that opened into the scrotum.…”
Section: Dovepressmentioning
confidence: 99%
“…Lopes and his colleagues reported that the type of UD was associated with the number of surgeries needed and the postoperative complication rate. 17 Mane SB et al described a single-stage repair protocol in which the buccal mucosa forms a tube for urethroplasty in cases of Y-duplication and reported it achieved good final outcomes. 18 Mori et al described a case treated with complete excision of the accessory urethra from the normal urethra in a rare type IIA2 (Y-type) patient who had an accessory urethra that opened into the scrotum.…”
Section: Dovepressmentioning
confidence: 99%
“…Not much is known about embryogenesis of urethral duplication and various hypothesis exist 5 . The spectrum of presentation can vary depending upon the type of anomaly according to Effmann classification system 6 . If we talk about chordee, it is more common on ventral side and often associated with hypospadia.…”
Section: Discussionmentioning
confidence: 99%
“…11 En la duplicación uretral tipo I, la falla embriológica detectada es probablemente secundaria a la falla del desarrollo del tabique urorrectal. 10,[12][13][14] Algunos autores consideran que los casos con el tipo I (A o B) cuando son asintomáticos no tienen indicación quirúrgica. 14,15 Pero si presenta secreción se tendrá que realizar la exéresis de la uretra accesoria.…”
Section: Discussionunclassified
“…10,[12][13][14] Algunos autores consideran que los casos con el tipo I (A o B) cuando son asintomáticos no tienen indicación quirúrgica. 14,15 Pero si presenta secreción se tendrá que realizar la exéresis de la uretra accesoria. 10,16 Otra opción es una neouretroplastia descrita por Podesta.…”
Section: Discussionunclassified